State-to-state chemistry and rotational excitation of CH+ in photon-dominated regions - Faure, A.; Halvick, P.; Stoecklin, T.; Honvault, P.; Epee, M. D. Epee; Mezei, J. Zs.; Zanchet, A. (Oxford Univ Press, 2017)
We present a detailed theoretical study of the rotational excitation of CH+ due to reactive and non-reactive collisions involving C+(P-2), H-2, CH+, H and free electrons. Specifically, the formation of CH+ proceeds through the reaction between C+(P-2) and H-2(vH(2) = 1, 2), while the collisional (de)excitation and destruction of CH+ is due to collisions with hydrogen atoms and free electrons. State-to-state and initial-state-specific rate coefficients are computed in the kinetic temperature range 10-3000 K for the inelastic, exchange, abstraction and dissociative recombination processes using accurate potential energy surfaces and the best scattering methods. Good agreement, within a factor of 2, is found between the experimental and theoretical thermal rate coefficients, except for the reaction of CH+ with H atoms at kinetic temperatures below 50 K. The full set of collisional and chemical data are then implemented in a radiative transfer model. Our non-LTE calculations confirm that the formation pumping due to vibrationally excited H-2 has a substantial effect on the excitation of CH+ in photon-dominated regions. In addition, we are able to reproduce, within error bars, the far-infrared observations of CH+ towards the Orion Bar and the planetary nebula NGC 7027. Our results further suggest that the population of vH(2) = 2 might be significant in the photon-dominated region of NGC 7027.
Keywords: astrochemistry; line: formation; molecular data; molecular processes; radiative transfer; ISM: molecules